2014
DOI: 10.1007/s00784-014-1348-5
|View full text |Cite
|
Sign up to set email alerts
|

MTA versus Ca(OH)2 in apexification of non-vital immature permanent teeth: a randomized clinical trial comparison

Abstract: Apexification using MTA seems preferable to CH in order to early achieve the coronoradicular filling and to limit the risk of root fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 24 publications
5
77
0
6
Order By: Relevance
“…ability, and their setting is not greatly affected by moisture (Camilleri 2015, Prati & Gandolfi 2015. The use of MTA for various endodontic applications such as direct pulp capping (Okiji & Yoshiba 2009, Li et al 2015, root-end filling (C ßalıs ßkan et al 2016), perforation repair (Krupp et al 2013) and apical barrier formation in teeth with open apexes (Bonte et al 2015) is reported to result in promising clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…ability, and their setting is not greatly affected by moisture (Camilleri 2015, Prati & Gandolfi 2015. The use of MTA for various endodontic applications such as direct pulp capping (Okiji & Yoshiba 2009, Li et al 2015, root-end filling (C ßalıs ßkan et al 2016), perforation repair (Krupp et al 2013) and apical barrier formation in teeth with open apexes (Bonte et al 2015) is reported to result in promising clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…, Bonte et al . ). In the present prospective randomized comparative clinical study, in addition to strict patient enrolment criteria, a standardized clinical treatment protocol was established as follows: care was taken not to overextend the instrumentation, disinfection of the root canal was provided with NaOCI, EDTA and finally CHX, CH paste was kept in contact with the periapical tissues and changed until occurrence of apical barrier formation for CH group, whilst CH paste was used in the MTA group for a week.…”
Section: Discussionmentioning
confidence: 97%
“…, Bonte et al . ), a physical apical barrier was not used and MTA was placed gently step by step with radiographic examination, and the location of the MTA was checked immediately after placement. In the present study, a similar protocol was utilized and careful radiographic examination was performed during the placement of the MTA in order to prevent its extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MTA yields favorable results when used as retrofilling material, allowing the formation of mineralized tissue 32,33 and presenting no inflammation. For instance, MTA can be used in the pulpectomy of both deciduous and permanent teeth or as an apical barrier in teeth with pulp necrosis and open apices, with or without previous treatment with sodium hydroxide.…”
Section: Discussionmentioning
confidence: 99%